Oligoproline-derived nanocarrier for dual stimuli-responsive gene delivery1. Issue 36 (28th September 2015) - Gupta, Mukesh K.; Lee, Sue Hyun; Crowder, Spencer W.; Wang, Xintong; Hofmeister, Lucas H.; Nelson, Christopher E.; Bellan, Leon M.; Duvall, Craig L.; Sung, Hak-Joon
<x xml:space="preserve">Abstract</x> Illustration of extracellular ROS mediated dePEGylation of polyplexes and delivery of pDNA triggered by endosomal pH (5.0).